Cis-Regulatory Logic Produces Gene-Expression Noise Describing Phenotypic Heterogeneity in Bacteria - Chowdhury, Debajyoti; Wang, Chao; Lu, Aiping; Zhu, Hailong (Frontiers in Genetics, 2021)
Gene transcription is random; it follows single-molecular kinetics and occurs in bursts. Intermittent bursts are measured based on their frequency and size, and these bursts influence temporal fluctuations in the total mRNA and protein abundance and induce distinct transcriptional variations referred to as “noise”. Noisy expression induces uncertainty because the association between transcriptional variation and the extent of gene expression fluctuation is ambiguous. The promoter architecture and remote interference of different cis-regulatory elements are crucial determinants of noise, which is reflected in phenotypic heterogeneity. An alternative perspective considers that cellular parameters dictating genome-wide transcriptional kinetics follow a universal pattern. Research on noise and systematic perturbations of promoter sequences reinforces that both gene-specific and genome-wide regulation occur across species ranging from bacteria and yeast to animal cells. Thus, deciphering gene-expression noise is essential in genomics and clinical applications; amidst mounting conflict, it is imperative to reconsider the scope, progression, and logical construction of diversified viewpoints underlying the origin of noise. It is also crucial to combat antibiotic resistance. We established a consolidated indication connecting noise, gene expression variations, and bacterial phenotypic variability. This review will enhance our understanding of gene-expression noise in various scientific contexts and applications.